2011
DOI: 10.1371/journal.pone.0026702
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Independent Behavior and Membrane Deformation Exhibited by the Four-Transmembrane Protein M6a

Abstract: M6a is a four-transmembrane protein that is abundantly expressed in the nervous system. Previous studies have shown that over-expression of this protein induces various cellular protrusions, such as neurites, filopodia, and dendritic spines. In this detailed characterization of M6a-induced structures, we found their varied and peculiar characteristics. Notably, the M6a-induced protrusions were mostly devoid of actin filaments or microtubules and exhibited free random vibrating motion. Moreover, when an antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
4
10
0
Order By: Relevance
“…We postulate that the GPM6 glycoproteins may form a protein pore, perhaps through oligomeric interactions, which have been proposed previously 35,44 . In the right conformation, proteasomes binding to pore-containing membrane proteins could give proteasomes a hydrophilic binding surface to the hydrophobic plasma membrane, allowing the proteasome to gain access to the extracellular space.…”
Section: Discussionsupporting
confidence: 55%
“…We postulate that the GPM6 glycoproteins may form a protein pore, perhaps through oligomeric interactions, which have been proposed previously 35,44 . In the right conformation, proteasomes binding to pore-containing membrane proteins could give proteasomes a hydrophilic binding surface to the hydrophobic plasma membrane, allowing the proteasome to gain access to the extracellular space.…”
Section: Discussionsupporting
confidence: 55%
“…In conclusion, in the last 10 years, various cellular, anatomical, and pathological alterations have been associated with neuronal glycoprotein M6a, whose mechanism of action is still unknown. Sato et al described the critical role of the TMD1 of M6a in inducing tubular processes in COS-7 cells (Sato et al 2011b). This work provides the first evidence of the critical role of certain residues located on TMD2 and TMD4 of M6a in the mechanism of action and the potential risk of the SNPs reported here, particularly SNP3.…”
Section: ###supporting
confidence: 65%
“…Previous study showed that the over-expression of M6a enhanced the formation of membrane protrusions (Sato et al, 2011b) and filopodia/spine (Alfonso et al, 2005;Brocco et al, 2010).…”
Section: Functional Domains Of M6a For the Axonal Growthmentioning
confidence: 92%
“…For the formation of membrane protrusions, the N-terminus domain (amino acid 1-62) of M6a is required (Sato et al, 2011b). For the formation of filopodia/spine, the second extracellular domain (C174 and C192) is essential (Fuchsova et al, 2009).…”
Section: Functional Domains Of M6a For the Axonal Growthmentioning
confidence: 99%